2002
DOI: 10.1557/proc-717-c4.6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluorine on the Diffusion of Boron in Amorphous Silicon

Abstract: Fluorine and boron co-implantation within amorphous silicon has been studied in order to meet the process challenges regarding p+ ultra-shallow junction formation. Previous experiments have shown that fluorine can reduce boron TED (Transient Enhanced Diffusion), enhance boron solubility and reduce sheet resistance. In this study, boron diffusion characteristics prior to solid phase epitaxial regrowth (SPER) of the amorphous layer in the presence of fluorine are addressed. Samples were pre-amorphized with Si+ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…However, there have also been contradictory reports in the literature, which showed that fluorine implants had little or no effect on boron diffusion 12 and even enhanced boron diffusion in amorphous silicon. 13 While there has been considerable research on the effect of fluorine on TEBD, little has been published on the effects of fluorine on the thermal diffusion of boron. In this letter, a study is made of the effect of fluorine on the diffusion of boron in buried marker layers.…”
mentioning
confidence: 99%
“…However, there have also been contradictory reports in the literature, which showed that fluorine implants had little or no effect on boron diffusion 12 and even enhanced boron diffusion in amorphous silicon. 13 While there has been considerable research on the effect of fluorine on TEBD, little has been published on the effects of fluorine on the thermal diffusion of boron. In this letter, a study is made of the effect of fluorine on the diffusion of boron in buried marker layers.…”
mentioning
confidence: 99%
“…[4][5] However, when samples are preamorphized with germanium, dissimilar results are obtained under the same dopant implantation and annealing processes. [4][5] However, when samples are preamorphized with germanium, dissimilar results are obtained under the same dopant implantation and annealing processes.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] This research has been motivated by the requirement in advanced CMOS technologies to minimize boron diffusion for the formation of shallow source/drain junctions and sharply defined halo profiles. 19,20 The minimization of boron diffusion is also important in bipolar transistors, where boron diffusion limits the achievable base width and hence the value of cutoff frequency that can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…2 However, there have also been contradictory reports in the literature, which showed that fluorine implants had little or no effect on boron transient enhanced diffusion 10 and that fluorine enhanced boron diffusion in preamorphized silicon 6 using a silicon implant. 15 Recently El Mubarek and Ashburn 18 showed that a deep F + implant significantly reduced boron thermal diffusion, as well as eliminating transient enhanced diffusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation